Prospects of using unmanned aerial vehicles for detecting fossil mammoth ivory fields in the Arctic - A. N. Smirnov; K. K. Kalinovskii; N. V. Glinskaya; I. S. Dergacheva; M. A. Kalinovskaia; V. V. Petrov; А. Н. Смирнов; К. К. Калиновский; Н. В. Глинская; И. С. Дергачёва; М. А. Калиновская; В. В. Петров (Государственный научный центр Российской Федерации Арктический и антарктический научно-исследовательский институт, 2024)
In recent decades, fossil ivory, the tusks of the Siberian mammoth of the late type (Mammuthus primigenius Blumenbach, 1799), has been in great demand on the world market of gemstone raw materials. Fossil ivory is a valuable highly liquid natural raw material of biogenic origin. With its decorative and technological characteristics, it is a fossil analogue of the tusks of the present-day African and Asian elephant (the populations of which are protected by UNESCO), used for the production of carved articles of great aesthetic value. Industrial clusters of mammoth tusks are concentrated in just a few Arctic regions of Russia: the only region today which holds confirmed industrial potential of fossil mammoth ivory (actually recoverable resources) is Northern Yakutia. This is due to the limited number of territories whose paleogeographic and landscape-ecological conditions were favorable for mammoths in the Late Pleistocene, as well as to the taphonomic conditions conducive to the long-term preservation of bone remains in permafrost conditions. Placer accumulations of mammoth tusks are formed as a result of denudation of cryogenic bone reservoirs containing up to 90% ice; the main destructive factors are various types of thermal erosion, which contributes to the formation of new accumulations. Today, just as centuries ago, the search for fossil ivory, is carried out mainly by walking over large areas in remote areas of the Russian Arctic. The search objects are fully or partially exposed fossil ivory lying on the surface (in the surface layer) of present-day sedimentary formations in various landscape-geomorphological and geobotanical settings. The current period of studying and exploiting the natural resources in Russia is characterized by the active use of unmanned aerial vehicles (UAVs) with video cameras, which significantly reduces the complexity of research in various fields of their application. We have carried out experimental and methodological work for the visual recognition of exposed mammoth tusks in ...